Faktor-Faktor Penyebab Terjadinya Temuan Berulang Atas Pemeriksaan Oleh Inspektorat Kota Gorontalo - Nunu, Indrawati; Sondakh, Jullie; Pontoh, Winston (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. This study aims to determine the factors that cause the occurrence of recurring findings on the Inspectorate check and to analyze the coaching role of the Inspectorate in order to minimize the recurring findings. The recurring findings are the findings with same problems, which are repetitive from year to year although the previous findings have been resolved. The recurring findings are not only in the form of the loss of the local government, but also in terms of the administrative arrangement including the aspects of financial management, personnel management, the implementation of the basic tasks and functions, and the management of local government asset. The priciple theory used for this study includes the agency theory, positive accounting theory, compliance theory, attribution theory, and the theory of organizational commitment. This research employs a qualitative method and an exploratory approach. This approach elaborates more about the research topic based on the information collected from the interviews with the participants. These data were triangulated with other data obtained from observation and document analysis and then, they were analyzed interactively by reducing, presenting in the form of texts and tables, and making a conclusion. The result shows that the factors that cause recurring findings on the examination of the Inspectorate from the auditors’ side are: 1) lack of coordination and communication in the audits; 2) lack of auditor competence in developing the findings. On the contrary, from the side of the auditee, the factors are: 1) the lack of coordination and communication in the audits; 2) lack of integrity and ethical values; 3) weak internal control systems; 4) lack of management commitment; 5) mutation of the financial managers; and 6) regulatory changes. Inspectorate has made various efforts to minimize their recurring findings in the form of guidance to the Local Government Unit, but in fact it can be said not effective. Suggestion that can be given to the auditor/head of the Inspectorate is to improve the communication and coordination with the object of examination and other related SKPD as well as to enhance the competence, especially in developing the audit findings. In addition, the leaders of SKPD (auditee) should be more active in making further coordination with the inspectorate, controlling the application of SPIP and creating the Standard Operating Procedure (SOP) for each activity. Keywords: Recurring findings, Guidance, Inspectorate. Abstrak. Penelitian ini bertujuan untuk mengetahui faktor-faktor penyebab terjadinya temuan berulang atas pemeriksaan Inspektorat serta menganalisis peran pembinaan Inspektorat dalam upaya meminimalisir adanya temuan berulang. Temuan berulang adalah temuan dengan permasalahan yang sama, yang selalu berulang dari tahun ke tahun walaupun temuan sebelumnya telah ditindaklanjuti. Temuan berulang yang dimaksud tidak hanya dalam bentuk kerugian daerah namun juga dari sisi penataan administrasi baik dari aspek pengelolaan keuangan, pengelolaan aparatur, pelaksanaan tugas pokok dan fungsi, dan pengelolaan aset daerah. Teori dasar yang digunakan dalam penelitian ini meliputi teori keagenan, teori akuntansi positif, teori kepatuhan, teori atribusi, dan teori komitmen organisasi. Penelitian ini merupakan jenis penelitian metode kualitatif dengan pendekatan eksploratori. Pendekatan ini bertujuan untuk mencari tahu lebih dalam mengenai topik penelitian berdasarkan informasi yang dikumpulkan dari narasumber melalui wawancara. Data ini ditriangulasikan dengan data lain yang diperoleh dari observasi dan studi dokumentasi, kemudian dianalisis secara interaktif dengan mereduksi, menyajikan dalam bentuk teks dan tabel, dan membuat suatu kesimpulan. Hasil penelitian ini menunjukkan bahwa faktor-faktor yang menyebabkan terjadinya temuan berulang atas pemeriksaan Inspektorat dari sisi auditor adalah: 1) kurangnya koordinasi dan komunikasi audit; 2) kurangnya kompetensi auditor dalam pengembangan temuan. Sedangkan dari sisi auditi adalah: 1) kurangnya koordinasi dan komunikasi audit; 2) kurangnya integritas dan nilai etika; 3) lemahnya sistem pengendalian intern; 4) tidak adanya komitmen pimpinan; 5) adanya mutasi pengelola keuangan; dan 6) perubahan regulasi. Inspektorat telah melakukan berbagai upaya dalam meminimalisir adanya temuan berulang dalam bentuk pembinaan kepada Satuan Kerja Pemerintah Daerah (SKPD), namun pada kenyataannya dapat dikatakan belum efektif. Saran yang dapat diberikan bagi auditor/pimpinan Inspektorat adalah memperbaiki komunikasi dan koordinasi dengan objek pemeriksaan dan SKPD terkait lainnya serta lebih meningkatkan kompetensinya terutama dalam hal pengembangan temuan audit. Sedangkan untuk pimpinan SKPD (auditi) diantaranya lebih aktif dalam melakukan koordinasi lebih lanjut dengan Inspektorat, melakukan pengendalian dalam bentuk penerapan SPIP dan membuat Standar Operasional Prosedur (SOP) untuk setiap kegiatan. Kata Kunci : Temuan berulang, Pembinaan, Inspektorat.